2018
DOI: 10.1080/14036096.2018.1510854
|View full text |Cite
|
Sign up to set email alerts
|

Moving House and Housing Preferences in Older Age in Slovenia

Abstract: Various studies indicate that the elderly are unwilling to move, while health issues are one of the important factors influencing decisions to move. In our study, we tested the willingness of the elderly to accept various housing options based on a large quantitative survey of persons aged 50 and above conducted in 2015 in Slovenia. Our focus was on the respondents' attitudes to different housing options, especially less-wellknown options such as senior cohousing, household groups, family caregiving for elderl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Post-communist central and eastern European counties like Slovenia should (continue to) develop various housing options for older people. This is not only needed due to the accelerated ageing of the population, but also because of the younger generations of older people who are open to various housing opportunities in old age, as this study indicated (see also Filipovič Hrast et al [20]). Because older people are mostly attached to their home environment and satisfied with it, priority should be given to ageing in place and to ensuring that older people can remain in their home environment for as long as possible.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Post-communist central and eastern European counties like Slovenia should (continue to) develop various housing options for older people. This is not only needed due to the accelerated ageing of the population, but also because of the younger generations of older people who are open to various housing opportunities in old age, as this study indicated (see also Filipovič Hrast et al [20]). Because older people are mostly attached to their home environment and satisfied with it, priority should be given to ageing in place and to ensuring that older people can remain in their home environment for as long as possible.…”
Section: Discussionmentioning
confidence: 63%
“…This study took place within central and eastern Europe, a region with high rates of home ownership [17] but relatively poor development of long-term care services to support ageing in place with a high quality of life [18,19]. In Slovenia, these characteristics are combined with a low availability of alternative housing options [20] and a traditionally well-developed institutional sector (i.e., care homes [21]); however, care homes are often perceived as the least preferred option [9] and also an increasingly expensive one [22]. These conditions frame an important context of a high reluctance to move from an individual home even though the support for remaining there is low, and this can have important implications for the quality of ageing in place.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18,36]. It should also be pointed out that seniors in Poland, as in many other countries (e.g., Austria, Germany, Slovenia), are not willing to change their place of residence; they would prefer to stay in the currently occupied housing units, and adapt those residences to their housing needs [18,32,33,53,54].…”
Section: Methodsmentioning
confidence: 99%
“…In a survey of the housing preferences of people over 50 years of age, the types of housing construction for seniors that could potentially be of interest to seniors were identified. It was indicated that seniors and pre-senior citizens often do not know the available housing options and a survey of housing preferences will allow for the adjustment of housing policies to the housing needs of senior citizens [32]. In Germany, the housing preferences of people in pre-retirement age in 10 cities were also studied, with the primary aim of determining whether the respondents considered changing their place of residence in the future or preferred to stay in their current dwelling [33].…”
Section: Overview Of Existing Studiesmentioning
confidence: 99%
“…Despite the preferred option for frail individuals is aging in their own home (Eurobarometer, 2007 ; Filipovič Hrast, Sendi, Hlebec, & Kerbler, 2019 ), not everyone manages to do it. The availability of beds in nursing homes, as well as measures aimed at increasing the means-testing, could open avenues for inequalities in the composition of nursing home residents.…”
Section: Introductionmentioning
confidence: 99%